2018
DOI: 10.1016/j.kjms.2018.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and vaspin in patients with bipolar disorder

Abstract: Metabolic disorders and abnormal levels of circulating adipokines have been reported in patients with bipolar disorder (BD). The aim of this study was to investigate the differences in the correlations of vaspin plasma levels and metabolic parameters between two groups: patients with BD and mentally healthy persons. We measured plasma levels of vaspin, metabolic parameters, and metabolic syndrome (MS) in 101 patients with BD and 90 healthy control (HC) subjects. Patients with BD were evaluated with the Young M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
(45 reference statements)
1
0
0
Order By: Relevance
“…In this study, obesity indicators such as BMI and waist circumference of BD patients were higher than the control group. Ertekin et al,35 have found similar alcohol use, smoking, and obesity rates compared to our findings. Obesity is more prevalent in BD patients compared to the average population.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, obesity indicators such as BMI and waist circumference of BD patients were higher than the control group. Ertekin et al,35 have found similar alcohol use, smoking, and obesity rates compared to our findings. Obesity is more prevalent in BD patients compared to the average population.…”
Section: Discussionsupporting
confidence: 89%